Den observerade undervisningens betydelse i trepartssamtalet: grund för bedömning eller exempel för analys? - Gustavsson, Susanne; Gyllspång, Ingela; Hellgren, Helena; Ståhlfors, Gunilla (Educare, 2025)
This study addresses the practicum (VFU) component in teacher education, which traditionally involves a university-affiliated teacher observing the student’s teaching on a single occasion during the practicum course. This observation serves as a basis for a subsequent follow-up discussion meeting, and in some cases, contributes to the final formal assessment examination of the student. The aim of this study is to examine how the observed teaching is represented and utilized during these discussion meetings, focusing on how it informs the conversation and what assessment aspects emerge in relation to the observation. The empirical data consists of eight recorded VFU observation follow-up meetings, and the analysis is guided by critical hermeneutics. The results show that while the observed teaching is referenced during the discussions, it becomes secondary to other topics. Assessment tends to center on relational and leadership competencies, with less emphasis on an in-depth didactic discussion. This study’s discussion section reflects on the implications of these findings, particularly regarding the value of observed teaching for student teachers’ knowledge development, and for its function with the assessment process during the practicum.